SEISMIC PATTERN BASED ON ANALYSIS OF FRACTAL VARIATIONS BEFORE THE 2009 SUMATRA EARTHQUAKE WITH ZMAP SOFTWARE - Rafki Imani (JISTech (Journal of Islamic Science and Technology), 2019)
The Sumatra-Andaman earthquake of December 26, 2004, to Padang earthquake on September 30, 2009, was a series of destructive earthquakes in the history of the Sumatra earthquake. This research is aimed at earthquake mitigation by determining the patterns and earthquake phenomena before the 2009 Padang Earthquake with fractal dimensions D based on the Maximum Likelihood Estimation (MLE) by Gutenberg-Richter as an effort to predict earthquakes in anticipation period (pre-disaster) with the help of Zmap software. Seismic data was taken from NEIC-USGS and BMKG until November 2013 with an area limit of 92o BT - 106o BT and 7o LU - 7o LS, at a maximum earthquake depth of 200 km, which contains the Sumatra region. The estimation results explain the temporary decrease in fractal D seen and began to rise again before the significant earthquake in The 2009 Padang Earthquake